Field measurement of air velocity and temperature factors that influence the thermal comfort in shuttle bus - Arasinah Kamis (Tanjung Malim, 2023)
Field measurement of air velocity and temperature factors that influence the thermal comfort in shuttle bus by Arasinah Kamis